The blood-brain barrier in primary CNS lymphomas: ultrastructural evidence of endothelial cell death. - Molnár, P. P. (1999)
The vasculature of 24 primary CNS B-cell lymphomas that were not related to acquired immunodeficiency syndrome was systematically studied by electron microscopy. Seven low-grade astrocytic tumors were included for comparison. Classical electron microscopy features of apoptosis were found in lymphoma cells of 21 of 22 subjects. Capillaries of gliomas and lymphomas showed changes reported previously: variability of endothelial cell (EC)-thickness and number, basal lamina thickness and duplication, and fenestrations. Primary CNS B-cell lymphoma ECs showed two distinctive populations of electron-dense and electron-lucent cells. The electron-dense ECs occurred in 38% of all capillaries, with changes consisting of chromatin condensation in bizarre and contracted nuclei, cytoplasmic shrinkage with markedly increased electron density, and dilatation of the endoplasmic reticulum. We interpreted these changes as indicative of apoptosis. Cell death eventually resulted in complete disintegration of the endothelium with frank discontinuities of the EC component of the blood-tumor barrier in capillaries and postcapillary venules. Another population of ECs had increased cell volume, conspicuous cytoplasmic electron lucency, dispersed organelles, scattered vesicles, and apical stress fibers. We interpreted these changes as indicative of cellular regeneration. Individual apoptotic ECs often lay next to normal or regenerating ECs. Neither type of EC change was observed in gliomas, which also lacked perivascular neoplastic lymphocytic cuffing. We believe that these populations of ECs, which have not been described in other disorders affecting the blood-brain barrier, may be induced by cytokines released from necrotic and/or apoptotic tumor lymphocytes and may explain the unusual imaging characteristics of primary CNS B-cell lymphomas treated with corticosteroids.